The contemporary English-Filipino dictionary - Constantino, Ernesto Andres (EAC Center for Philippine Languages, 1999)
This dictionary contains English-Filipino words and phrases, translations, spellings, inflections and some Filipino abbreviations. It aims to assist Filipinos in shifting linguistically from English to Filipino to fully understand the meaning and uses of English words and phrases. It also shows the equivalents for English words and phrases which Filipinos commonly use.